Glia and zinc in ageing and Alzheimer’s disease: a mechanism for cognitive decline? - Hancock, Sara M.; Finkelstein, David I.; Adlard, Paul A. (Frontiers in Aging Neuroscience, 2014)
Normal ageing is characterised by cognitive decline across a range of neurological functions, which are further impaired in Alzheimer’s disease (AD). Recently, alterations in zinc concentrations, particularly at the synapse, have emerged as a potential mechanism underlying the cognitive changes that occur in both ageing and AD. Zinc is now accepted as a potent neuromodulator, affecting a variety of signalling pathways at the synapse that are critical to normal cognition. While the focus has principally been on the neuron: zinc interaction, there is a growing literature suggesting that glia may also play a modulatory role in maintaining both zinc ion homeostasis and the normal function of the synapse. Indeed, zinc transporters have been demonstrated in glial cells where zinc has also been shown to have a role in signalling. Furthermore, there is increasing evidence that the pathogenesis of AD critically involves glial cells (such as astrocytes), which have been reported to contribute to amyloid-beta neurotoxicity. This review discusses the current evidence supporting a complex interplay of glia, zinc dyshomeostasis and synaptic function in ageing and AD.